Impedance-based temperature measurement method for organic light-emitting diodes (OLEDs). (July 2018) - Raijmakers, L.H.J.; Büchel, M.; Notten, P.H.L.
Abstract: This short communication presents a method to measure the integral temperature of organic light-emitting diodes (OLEDs). Based on electrochemical impedance measurements at OLEDs, a non-zero intercept frequency (NZIF) can be determined which is related to the OLED temperature. The NZIF is defined as the frequency at which the imaginary part of the impedance is equal to a predefined (non-zero) constant. The advantage of using an impedance-based temperature indication method through an NZIF is that no hardware temperature sensors are required and that temperature measurements can be performed relatively fast. An experimental analysis reveals that the NZIF is clearly temperature dependent and, moreover, also DC current dependent. Since the NZIF can readily be measured this impedance-based temperature indication method is therefore simple and convenient for many applications using OLEDs and offers an alternative for traditional temperature sensing.